A sustainable solution to manage ecosystem health of wetlands in urban and peri-urban areas of Lucknow district, India using geospatial techniques and community based pragmatic approach - Kashif Imdad; Mehebub Sahana; Joe Ravetz; Gopala Areendran; Ouseen Gautam; Sudha Dwivedi; Archana Chaudhary; Haroon Sajjad (J. Clean Prod., 2023)
Wetlands are multi-functional landscapes between terrestrial and aquatic ecosystems that provide habitat for wildlife, support groundwater recharge, moderate climate, control flood and fulfil the livelihood of the com-munities. Rapid population growth, urban expansion, and industrialization have caused the degradation of wetlands over the last few decades. The wetlands located in the urban and peri-urban areas are generally the most threatened ecosystems globally. The present study assessed the ecosystem health of urban and peri-urban wetlands of Lucknow district in India and recommended a sustainable solution for their management. Remote sensing data derived from the normalized difference vegetation index, modified normalized difference water index, and land use/land cover change were utilized for analyzing the spatiotemporal change in areas under wetlands, from 1989 to 2018. Site-specific indicators on pressure, state and response were integrated in FRAGSTATS-based assessment to construct a Pressure-State-Response (PSR) model. A qualitative field survey has been conducted through focus group discussion and expert opinion to validate the result from the PSR model. The results revealed that the overall health of the wetlands has deteriorated drastically in these peri-urban areas owing to anthropogenic activities. The wetland ecosystem's health is significantly correlated with land trans-formation. The study recommended community participation, and involvement of local authorities in storing rainwater, constructing culverts and channels, and interlinking them with wetlands for sustainable conservation and effective management of the wetland ecosystem.
Keywords: Abortion; Reproductive Health; Maternal and child health